Practices and concepts of integrated education system in selected Islamic religious schools in the Malay archipelago - Abd Rashid, Adnan; Othman, Azam; Hussien, Suhailah; Sheikh Ahmad, Ismail; Badzis, Mastura (worldconferences.net, 2013)
This paper discusses the practices and concepts of integrated education system in selected Islamic integrated schools in the Malay Archipelago, the underlying factors and issues regarding the schools’ leadership and management. Semi-structured interviews were conducted with the participants, namely school leaders and teachers. Preliminary findings suggest that the teachers and the schools leaders have positive perceptions on the concept, practices and implementation of Islamic Integrated schools. Furthermore, it was observed that these schools were committed to deliver the best level of quality Islamic education by improving their teachers’ teaching skills and through a leadership style that engenders commitment from the teachers. The findings revealed a number of important implications for the future development of the Islamic integrated schools in order to continuously serve the needs of the students, the parents, and the Muslim ummah.